Study protocol - Prospective case-control trial - Impact of significant carotid stenosis on retinal perfusion measured with automated retinal oximetry - Polidar, Petr; Paskova, Barbora; Karhanova, Marta; Sin, Martin; Dornak, Tomas; Schreiberova, Zuzana; Divisova, Petra; Veverka, Tomas; Franc, David; Sanak, Daniel; Kral, Michal (Biomedical papers, 2025)
Background. Large vessel carotid stenosis is a significant cause of ischaemic stroke. Indications for surgical revascularisation depend on the severity of the stenosis and clinical symptoms. However, mild symptoms such as TIA (Transient ischaemic attack), amaurosis fugax or minor stroke precede large strokes in only 15% of cases. Aim. The aim of this prospective study is to evaluate whether retinal perfusion is impacted in significant carotid stenosis. Automated retinal oximetry will be used to better assess perfusion in the post-stenotic basin. We presume the more stenotic the blood vessel, the more reduced the retinal perfusion is, resulting in adaptive changes such as greater arteriovenous saturation difference due to greater oxygen extraction. This could broaden the indication spectrum for revascularisation for carotid stenosis. Methods. We plan to enroll yearly 50 patients with significant carotid stenosis and cross-examine them with retinal oximetry. The study group will provide stenotic vessels and, non-stenotic vessels will form the control group. Patients with significant carotid stenosis will undergo an MRI (Magnetic Resonnance imaging) examination to determine the presence of asymptomatic recent ischaemic lesions in the stenotic basin, and the correlation to oximetry parameters. Statistics. The stenosis severity and retinal oximetry parameters will be compared for study and control groups with a threshold of 70%, respectively 80% and 90% stenosis. Results will be then reevaluated with emphasis on MRI findings in the carotid basin. Conclusion. This prospective case control study protocol will be used to launch a multicentre trial assessing the relationship between significant carotid stenosis and retinal perfusion measured with automated retinal oximetry. Despite these differences, the findings indicate the potential of retinal oximetry for noninvasive real-time measurements of oxyhaemoglobin saturation in central nervous system vessels. Following calibration upgrade and technological improvement, verification retinal oximetry may potentially be applied to critically ill and anaesthesia care patients. The study on combined scanning laser ophthalmoscope and retinal oximetry supports the feasibility of the technique for oximetry analysis in newly born babies. Trial Registration: ClinicalTrials.gov, ID: NCT06085612
Keywords: ischaemic stroke; carotid stenosis; automated retinal oximetry; arterio-venous difference; magnetic resonance imaging